Virtual Care versus Traditional Clinical Visits Post COVID 19 Pandemic - Ahmed, Noha (European Journal of Applied Sciences, 2023)
The practice of treating a variety of medical illnesses without meeting the patient is known as telemedicine. Healthcare professionals can diagnose a patient’s condition and handle their issues remotely via telehealth platforms like live video, audio, or instant messaging. This can be offering them medical advice, guiding them through exercises they can do at home, or referring them to a nearby facility or provider. The development of telemedicine apps, which allow patients to get care directly from their phones or tablets, is even more intriguing. Of course, it can be difficult to manage some conditions remotely. Telemedicine is frequently utilized to deliver specialized services, manage chronic disorders, and treat common illnesses. The remote practitioner will advise a patient to seek in-person medical attention if they have an urgent or critical ailment. Virtual care is a broad phrase that refers to any form of distant patient interaction used by healthcare practitioners. This can be following up after an in-person appointment, keeping an eye on vitals following surgery, or answering any inquiries about their diagnosis, condition, or treatment strategy. Simply expressed, the phrase "virtual care" refers to all the ways that patients and doctors can interact digitally and in real-time. While virtual care is a much larger word that applies to a range of digital healthcare services, telemedicine refers to long-distance patient care. Physical patient care is a traditional health care method laying a strong foundational structure as compared to virtual care but nowadays specifically after the covid-19 outbreak a significant rise in virtual care setups has been seen and it is increasing way more swiftly than any other domain. One of the major reasons behind this accelerated shift is real-time access and cost-effectiveness of virtual setups reducing overall follow-up rates and waiting times. In a study by Herzer and Pronovost ( 2021) has depicted that using virtual care visits can reduce the entire cost of patient care for any suitable illnesses. (1)